A social identity model of riot diffusion: From injustice to empowerment in the 2011 London riots. (9th January 2020) - Drury, John; Stott, Clifford; Ball, Roger; Reicher, Stephen; Neville, Fergus; Bell, Linda; Biddlestone, Mikey; Choudhury, Sanjeedah; Lovell, Max; Ryan, Caoimhe
Abstract: Previous research has shown that riots spread across multiple locations, but has not explained underlying psychological processes. We examined rioting in three locations during the August 2011 disorders in England to test a social identity model of riot diffusion. We triangulated multiple sources to construct a narrative of events; and we analysed interviews with 68 participants to examine experiences. In line with the model, we found evidence for two pathways of influence: "cognitive" and "strategic". For some participants, previous rioting was highly self‐relevant, and shared identity was the basis of their subsequent involvement. For others, previous rioting was empowering because it demonstrated the vulnerability of a common enemy (the police). In each location, interaction dynamics mediated the link between initial perceptions and collective action. The utility of this social identity approach is that it is able to account for both the boundaries and the sequence of urban riot diffusion.